LES DISCUSSIONS SUR L’AVORTEMENT DANS LES ANNEES 2000 EN TURQUIE ET LES APPROCHES POLITIQUES - Sebnem Cansun (European Scientific Journal, ESJ, 2014)
This study aims at understanding how Turkish political parties perceive the subject of abortion, what differences there are between the approach of center-right and center-left parties as well as between men and women of the same parties. The parties in question are the conservativedemocratic AKP (the government party), the social-democratic CHP, the ultranationalist MHP, the pro-Kurdish BDP. The study focuses on party programs, electoral bulletins, declarations made by male and female politicians of these parties. Declarations of politicians are studied through Hürriyet (Liberty), a liberal national daily with an important circulation, from the last national election in 2011 to the present day. Abortion has been legal in Turkey since the 1980s, but the AKP brought it to Turkey’s agenda in 2012. In the programs and electoral bulletins, the AKP and the CHP treat the subject of birth control rather than that of abortion. The programs and the electoral bulletins of the MHP and the BDP comprise none of these, because they are rather pro-birth. Almost all the members of the AKP defend the prohibition of abortion except one female deputy. The CHP is for the legalization of abortion. The women of the CHP accuse the AKP of being despotic on this issue. The directors of the MHP and the co-president of the BDP do not take an open position but prefer criticizing the AKP. According to the data, center-right and center-left parties treat the subject of abortion differently. Some women of the center-right party position themselves to the left of the political spectrum than the men of their own party.